Cervical cancer and breast cancer - Poquioma Rojas, Ebert (2015)
Gynecologic cancer epidemiology in Peru. National program of promotion and cancer prevention. Role of centers of excellence in the prevention and treatment of cervical cancer. Scientific validity of the arguments against the HPV vaccine. Breast cancer in Peru.